Macroeconomics and Monetary Economics - 3: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
This study focuses on evaluating the monetary, fiscal and external inflationary sources in Nigeria. Empirical evidence suggests that the adoption of either monetary or fiscal policy or a synchronization of both policies appears to be very popular in Developing Nations like Nigeria. Often time, the policy choice that prevails is taken to be the sole cause of inflation in the economy. Such understanding has led to the obvious ambiguity in empirical literature centred on developing nations, regarding what the actual sources of inflation are. Thus, this study adopts the Auto Regressive Distributive estimation technique to capture the monetary, fiscal and external inflationary effects. Empirical findings of the study showed that overall, the main determining cause of inflation in both short run and long run periods in Nigeria, are more of monetary and external factors and less of fiscal sources. Specifically, the problem of inflation in Nigeria appears to be more of a structural phenomenon than monetary in the short run. However, in the long run, combinations of monetary and external factors tend to be the major cause of inflation. The study also found the long run effect of lending rate on inflation, to be indicative of the Neo-Fisherism effect.